2021
DOI: 10.1186/s13550-021-00797-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 18F-AlF-NOTA-octreotide for imaging neuroendocrine neoplasms: comparison with 68Ga-DOTATATE PET/CT

Abstract: Objective To evaluate the diagnostic efficacy of 18F-AlF-NOTA-octreotide (18F-OC) PET/CT compared with that of 68Ga-DOTATATE PET/CT. Materials and methods Twenty patients (mean age: 52.65 years, range: 24–70 years) with biopsy-proven neuroendocrine neoplasms (NENs) were enrolled in this prospective study. We compared the biodistribution profiles in normal organs based on the maximum standard uptake value (SUVmax) and mean standard uptake value (SUV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 19 publications
4
13
0
Order By: Relevance
“…In accordance with Hou et al (8), we observed considerable variability in lesion uptake both between and within patients. Differences in SSTR affinity profile between 18 F-AlF-OC and 68 Ga-DOTATATE/NOCto our knowledge, the exact affinity profile for 18 F-AlF-OC is still unknown in combination with NET heterogeneity may lie at the basis of this finding.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with Hou et al (8), we observed considerable variability in lesion uptake both between and within patients. Differences in SSTR affinity profile between 18 F-AlF-OC and 68 Ga-DOTATATE/NOCto our knowledge, the exact affinity profile for 18 F-AlF-OC is still unknown in combination with NET heterogeneity may lie at the basis of this finding.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, higher TBR values for 18 F-AlF-OC are mainly explained by significantly lower background uptake. In particular, the lower background uptake with 18 F-AlF-OC in the liver significantly improves detection of liver metastases as reflected by the high DDR value of 33.1% (95% CI: 21.7%-44.4%), which is consistent with previous observations (5,8). Tracer clearance may partly explain the lower background values for 18 F-AlF-OC, as 18 F-AlF-OC imaging was done at a later time point (2h p.i.)…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1,9,10 Several studies have shown that its detection rate of NET is highly consistent with that of 68 Ga-DOTATATE, which can be used for clinical staging. [10][11][12][13] Previous studies have shown that 18 F-NOTATATE is better than 18 F-FDG for imaging well-differentiated NET, whereas 18 F-FDG is better for imaging poorly differentiated NET. 1 However, this case is a poorly differentiated NEC, with marked 18 F-NOTATATE expression and equivocal FDG uptake.…”
Section: Figurementioning
confidence: 99%